Multiwavelength study of the luminous GRB 210619B observed with Fermi and ASIM. Issue 3 (12th December 2022) - Caballero-García, M D; Gupta, Rahul; Pandey, S B; Oates, S R; Marisaldi, M; Ramsli, A; Hu, Y-D; Castro-Tirado, A J; Sánchez-Ramírez, R; Connell, P H; Christiansen, F; Ror, A Kumar; et al.
ABSTRACT: We report on detailed multiwavelength observations and analysis of the very bright and long GRB 210619B, detected by the Atmosphere-Space Interactions Monitor installed on the International Space Station and the Gamma-ray Burst Monitor (GBM) on-board the Fermi mission. Our main goal is to understand the radiation mechanisms and jet composition of GRB 210619B. With a measured redshift of z  = 1.937, we find that GRB 210619B falls within the 10 most luminous bursts observed by Fermi so far. The energy-resolved prompt emission light curve of GRB 210619B exhibits an extremely bright hard emission pulse followed by softer/longer emission pulses. The low-energy photon index (αpt ) values obtained using the time-resolved spectral analysis of the burst suggest a transition between the thermal (during harder pulse) to non-thermal (during softer pulse) outflow. We examine the correlation between spectral parameters and find that both peak energy and αpt exhibit the flux tracking pattern. The late time broad-band photometric data set can be explained within the framework of the external forward shock model with ν m < ν c < ν x (where ν m, ν c, and ν x are the synchrotron peak, cooling-break, and X-ray frequencies, respectively) spectral regime supporting a rarely observed hard electron energy index ( p < 2). We find moderate values of host extinction of E ( B − V ) = 0.14 ± 0.01 mag for the small magellanic cloud extinction law. In addition, we also report late-time optical observations with the 10.4 m Gran Telescopio de Canarias placing deep upper limits for the host galaxy ( z  = 1.937), favouring a faint, dwarf host for the burst.